Faktor kemiskinan bandar terhadap pembangunan pendidikan golongan lewat kembang - Nor Azrul Mohd Zin; Noordeyana Tambi (Penerbit Universiti Kebangsaan Malaysia, 2018)
Currently, poverty is a growing issue in the urban community. The increasing cost of living, due to the rapid urbanisation process has resulted the urban community to forgo few vital interests in order to survive. The urban poverty’s condition can lead to more serious consequences when they decline the education rights of their children in order to survive rather than having a stable financial status. These pressing conditions have caused them to lack the proper education and become less successful in their careers compared to others. Thus, it has resulted in the late bloomers group who are forced to sacrifice their youth by working in order to obtain strong financial guarantee before resuming to get the perfect education just like everyone else at the later age. Hence, this paper will discuss solely based on past studies that have been conducted especially in Malaysia. The concepts and definitions of poverty and urban poverty will also be further discussed.